Dose–Sensitivity, Conserved Non-Coding Sequences, and Duplicate Gene Retention Through Multiple Tetraploidies in the Grasses - Schnable, James C.; Pedersen, Brent S.; Subramaniam, Shabarinath; Freeling, Michael (Frontiers in Plant Science, 2011)
Whole genome duplications, or tetraplodies, are an important source of increased gene content. Following whole genome duplication, duplicate copies of many genes are lost from the genome. This loss of genes is biased both in the classes of genes deleted and the subgenome from which they are lost. Many or all classes are genes preferentially retained as duplicate copies are engaged in dose sensitive protein-protein interactions, such that deletion of any one duplicate upsets the status quo of subunit concentrations, and presumably lowers fitness as a result. Transcription factors are also preferentially retained following every whole genome duplications studied. This has been explained as a consequence of protein-protein interactions, just as for other highly retained classes of genes. We show that the quantity of conserved non-coding sequences (CNSs) associated with genes predicts the likelyhood of their retention as duplicate pairs following whole genome duplication. As many CNSs likely represent binding sites for transcriptional regulators, we propose that the likelyhood of gene retention following tetraploidy may also be influenced by dose-sensitive protein-DNA interactions between the regulatory regions of CNS-rich genes -- nicknamed "bigfoot genes" – and the proteins that bind to them. Using grass genomes, we show that differential loss of CNSs from one member of a pair following the pregrass tetraploidy reduces its chance of retention in the subsequent maize-lineage tetraploidy.